STRATEGI PEMASARAN USAHA KECIL MENENGAH DI KABUPATEN BLITAR: (Studi Pada UKM Cap Kuda Terbang Bu Sulasmi) - Sunarsasi Sunarsasi; Nanang Rudi Hartono (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2020)
The purpose of this study is to determine the marketing strategy of UKM Sulasmi Cap Kuda Terbang. This research is to find out how the marketing strategy of UKM Sulasmi Cap Kuda Terbang and whether it has been running effectively or not. The research method used is using a qualitative approach so that it can develop and obtain in-depth research results. Data was obtained through an interview process with the owner of the Kuda terbang owner and direct observation of the business. Data obtained through interviews and subsequent observations will be analyzed to find out how the marketing strategy in UKM Sulasmi Cap Kuda Terbang and whether it has been effective or not. The results of the marketing strategy carried out by UKM Sulasmi Cap Kuda Terbang can be categorized as good. It's just that there are in some aspects that need to be improved. For example in the promotion aspect of UKM Sulasmi Cap Kuda Terbang not yet doing the right marketing strategy and only relying on the quality of its products, therefore it is necessary to improve marketing strategies through online media. Furthermore, in the process aspect, UKM Sulasmi Cap Kuda Terbang does not yet provide delivery order services, although this can increase sales while enhancing promotion strategies.